Mangrove Ecotourism Development In Central Maitara Village, North Tidore District (Agrikan Jurnal Agribisnis Perikanan, 2024)
This research aims to determine the role of the government in efforts to develop Mangrove ecotourism in Maitara Tengah Village, North Tidore District. This research uses a qualitative method with a descriptive approach, with the first stage being observation, interviews with 6 informants and documentation. The analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. The results of this research concluded that the role of the Central Maitara Village Government in developing mangrove ecotourism includes building supporting infrastructure for ecotourism, managing mangrove ecotourism through Bumdes, making appeals and inviting people to plant mangroves. With community involvement in the development of mangrove ecotourism including: selling around the mangrove ecotourism area, community service, and involvement as a mangrove ecotourism manager through BUMdes. Based on the conclusions above, it is recommended that the Central Maitara village government needs to build several additional infrastructure such as observation towers and information boards to support visitor activities while visiting the Central Maitara village mangrove ecotourism object and need to carry out training and coaching activities for the community in an effort to increase capacity. community in managing mangrove ecotourism.
Keywords: Mangrove; Ecotourism; Maitara